Release of Ferulic Acid from Banana Stem Waste by Ferulic Acid Esterase from Co-culture - Kamaliah, Abdul Samad; N., Zainol (IRJET, 2016)
The use of microbial in producing ferulic acid esterase for ferulic acid production from agricultural waste currently becomes important. This study was focus on investigating this capable enzyme from co-culture in releasing ferulic acid from banana stem waste by enzymatic hydrolysis. Submerged fermentation of banana stem waste by co-culture from Bacillus cereus, Bacillus pumilus, and Bacillus thuringiensis was conducted. The analysis found that ferulic acid yield gradually increased with the increasing of ferulic acid esterase activity until the late log phase or early stationary phase of co-culture growth. Ferulic acid esterase activity was increased up to 3.1-fold during the log phase and successfully released 571 mg/kg ferulic acid content. The discovery indicates that co-culture of Bacillus spp. have the capability of producing the desired enzyme in order to produce high-value compound from agricultural waste.